Пошаговое объяснение:
а) 4x + 4 = -12 в) 2(y + 3) = 21
4х=-12-4 2у+6=21
4х=-16 2у=21-6
х=-16/4 2у=15
х=-4 у=15/2
б) 7x - 6= x + 12 у=7,5
7х-х=12+6 г) 3(3х - 1) – х = 13.
6х=18 9х-3-х=13
х=18/6 8х=13+3
х=3 8х=16
х=16/8
х=2
Пошаговое объяснение:
а) 4x + 4 = -12 в) 2(y + 3) = 21
4х=-12-4 2у+6=21
4х=-16 2у=21-6
х=-16/4 2у=15
х=-4 у=15/2
б) 7x - 6= x + 12 у=7,5
7х-х=12+6 г) 3(3х - 1) – х = 13.
6х=18 9х-3-х=13
х=18/6 8х=13+3
х=3 8х=16
х=16/8
х=2
ответ:
1) 9|х|-2х-5|х|=8
|х|=8/2
|х|=4
х1=4
х2= -4
2)7|х|-2|х|-3|х|=12
2|х|=12
|х|=12/2
|х|=6
х1=6
х2= -6